Pengaruh Kecerdasan Emosional Dan Motivasi Belajar Siswa Terhadap Penguasaan Konsep Pembelajaran Geografi - Bukhari Muslim (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2018)
Abstract: The Influence of Emotional Intelligence and Student Learning Motivation on Mastery of Geography Learning Concept (Survey at SMA Negeri In Central Jakarta Region). This study aims to determine the extent to which the influence of emotional intelligence and student learning motivation on mastery of the concept of geography learning. If indeed there is a positive and significant influence then how strong the influence of emotional intelligence and student learning motivation to master the concept of learning geography. The research method used is survey with correlation and regression analysis, that is connecting between data showing emotional intelligence and student learning motivation with data showing mastery of geography learning concept. Data about emotional intelligence and student learning motivation is obtained through questionnaires prepared by the researcher, that is measuring matters relating to the above two things. While the data about the mastery of learning concepts on geography subjects obtained from test results on environmental materials and sustainable development. (1) There is a significant influence of emotional intelligence and learning motivation together on the mastery of the concept of geography learning, this is evidenced by the acquisition of Sig value. 0,000 <0,05 and F count 10,488. Together the variables of emotional intelligence and student learning motivation contributed 29.1% to mastery of the concept of geography learning. (2) There is a significant effect of emotional intelligence on the mastery of the concept of geography learning, this is evidenced by the acquisition of Sig value. 0,024 <0,05 and t count equal to 2,326. Emotional Intelligence variable contributed 11,09% in mastery of geography learning concept. (3) There is a significant influence of students' learning motivation on the mastery of the concept of geography learning, this is proved by the value of Sig. 0,003 <0,05 and t count 3,173. Student motivation variable contributes 18,04% in mastery of geography learning concept. Keywords: Emotional Intelligence, Learning Motivation, Concept Understanding